Antihypertensive Effect Of Magnesium Sulfate (Cormagnesin®) And Its Combination With Furosemide On Conscious Spontaneously Hypertensive Rats - Katerina Simeonova; Krassimir Dimitrov; Nikolay Danchev (Journal of Biomedical & Clinical Research)
The present study demonstrates the antihypertensive effect of magnesium sulfate (Cormagnesin®) and its combination with Furosemide on conscious spontaneously hypertensive rats (SHR) after intravenous infusion. Experiments were carried out on six groups of conscious male SHR (n=6). Under short anesthesia the rats were chronically instrumented for intravenous (i.v.) drug administration. The arterial blood pressure (AP) was measured by indirect tale method. Cormagnesin® was applied by i.v. infusion in doses of 5, 20 and 40 mg/kg; and furosemide (10 mg/kg) was applied intraperitoneally. Experimental results showed significant decrease of AP after i.v. infusion of 20 mg/kg Cormagnesin® as well as after application of the Cormagnesin® and furosemide combination. The hypotensive effects of 40 mg/kg Cormagnesin® and of furosemide were not significant. There was no significant difference between the antihypertensive effects of Cormagnesin® and its combination with furosemide but the combination showed much better hypotensive effect than Furosemide (p